Submillimeter alignment of more than three contiguous vertebrae in spinal SRS/SBRT with 6‐degree couch. (8th August 2017) - Wang, Xin; Zhao, Zhongxiang; Luo, Dershan; Yang, James N.; Yang, Jinzhong; Chang, Eric L.; Brown, Paul D.; Li, Jing; McAleer, Mary F.; Ghia, Amol J.
Abstract: The purpose of this study is to identify regions of spinal column in which more than three contiguous vertebrae can be reliably and quickly aligned within 1 mm using a 6‐degree (6D) couch and full body immobilization device. We analyzed 45 cases treated over a 3‐month period. Each case was aligned using ExacTrac x‐ray positioning system with integrated 6D couch to be within 1° and 1 mm in all six dimensions. Cone‐Beam computed tomography (CBCT) with at least 17.5 cm field of view (FOV) in the superior–inferior direction was taken immediately after ExacTrac positioning. It was used to examine the residual error of five to nine contiguous vertebrae visible in the FOV. The residual error of each vertebra was determined by expanding/contracting the vertebrae contour with a margin in millimeter integrals on the planning CT such that the new contours would enclose the corresponding vertebrae contour on CBCT. Submillimeter initial setup accuracy was consistently achieved in 98% (40/41) cases for a span of five or more vertebrae starting from T2 vertebra and extending caudally to S5. The curvature of spinal column along the cervical region and cervicothoracic junction was not easily reproducible between treatment and simulation. Fifty‐seven percent (8/14) of cases in this region had residual setup error of more than 1 mm in nearby vertebrae after alignment using 6D couch with image guidance. In conclusion, 6D couch integrated with image guidance is convenient and accurately corrects small rotational shifts. Consequently, more than three contiguous vertebrae can be aligned within 1 mm with immobilization that reliably reproduces the curvature of the thoracic and lumbar spinal column. Ability of accurate setup is becoming less a concern in limiting the use of stereotactic radiosurgery or stereotactic body radiation therapy to treat multilevel spinal target.